Hydraulic modelling in maritime engineering proceedings of the conference organized by the Institution of Civil Engineers, held in London on 13-14 October 1981. (Thomas Telford, 1982)
Focusing on model techniques used to study ship behaviour in canals and channels, these papers also offer a numerical analysis of sediment transport in coastal engineering problems, and physical models for coastal morphology and harbour problems.